ANALISIS POTENSI DAN HAMBATAN EKONOMI DIGITALDALAM MENGEMBANGKAN UMKM KOTA MEDANSUDUT PANDANG ETIKA BISNIS ISLAM - Siska Ramayani Damanik; Imsar Imsar; Reni Ria Armayani Hasibuan (CV. Denasya Smart Publisher, 2024)
This study aims to determine the potential and obstacles of the digital economy in developing MSMEs in the city of Medan and then reviewed from the perspective of Islamic business ethics. This study is a descriptive qualitative type that presents narrative data about objects found in the field. The subject of this study is the Medan City Cooperative and MSME Service and the object is the digital economy. This research is motivated by the Indonesian government's efforts to make MSMEs go digital coupled with the existence of a pandemic that forces economic activities to increasingly move towards digitalization so that MSMEs as a milestone in economic progress must actively move to follow the changing times. The data collection techniques used are interviews, observations, and documentation. The results obtained are: In the city of Medan, the digital economy system has been intensified for MSME actors, the Medan City Cooperative and MSME Service supports through consultation, training, and assisting MSME actors to develop their businesses digitally. Until now, there have been 3000 Medan City MSMEs that have registered as Fostered MSMEs at the Medan City Cooperative and MSME Service. This means that all the breakthroughs that have been made by the Medan City Cooperative and UMKM Service bring good news for the potential of the digital economy. However, in addition to all that, there are still many UMKM actors who are not aware of the digital economy, which is caused by low human resources, not yet technologically proficient, and still consider the system troublesome and choose to be stuck with a manual system.